FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAk) - Diah Puspitarini; Fariyana Kusumawati (InFestasi, 2011)
The goal this research is test influence of vactors to Student preference majoring in accounting to participation in accounting provetion program on four univercity: Unair, Ubaya, STIESIA, and Unibraw. Test of the research use linier regration model.The Result of the research, parsially test:  (a) independent variable significant infleance to dependent variable (carier motivation, kuality motivation, kwnoladge motivation, participating USAP motivation, degree motivation, term of education, and achievement motivation. (b) The cost of education motivation and econocic motivation don’t significant influence to participation in accounting provetion program. Corelation value R2 between independen variable and dependent and dependent variable is 0,894, determination value 0,790 is the meaning 79,0% participation in accounting provetion program influenced by independen variable, than 21,0% participation in accounting provetion program influenced by others variable.